2001
DOI: 10.1038/sj.onc.1204985
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α induces the expression of DR6, a member of the TNF receptor family, through activation of NF-κB

Abstract: The tumor necrosis factor (TNF) receptor family are ligand-regulated transmembrane proteins that mediate apoptosis as well as activation of the transcription factor NF-kB. Exogenous expression of DR6, a recently identi®ed member of the TNF receptor family, induced apoptosis in untransformed or tumor-derived cells and the apoptotic function of DR6 was inhibited by coexpression of Bcl-2, Bcl-x L or the inhibitor-of-apoptosis (IAP) family member, survivin. Expression of a dominant negative mutant of FADD failed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 40 publications
4
61
1
2
Order By: Relevance
“…Recently, nitric oxide-induced activation of p38 was implicated in triggering NF-kB-mediated expression of p53, leading to upregulation of the proapoptotic Bcl-2 family member Bax, just as cyanide-induced activation of NF-kB resulted in activation of the proapoptotic Bcl-xS and Bax proteins (Kim et al, 2002b;Shou et al, 2002). Other examples include NFkB-dependent activation of DR ligand TRAIL and TNF receptor family member DR6 (Baetu et al, 2001;Kasof et al, 2001;Rivera-Walsh et al, 2001;Siegmund et al, 2001). In one study, c-Rel induced expression of TRAIL receptors DR4 (TRAIL-R1), DR5 (TRAIL-R2) and the proapoptotic Bcl-2 family member Bcl-xS to sensitize cells to TRAIL-induced apoptosis .…”
Section: Mechanisms Through Which Nf-kb Promotes Cell Deathmentioning
confidence: 99%
“…Recently, nitric oxide-induced activation of p38 was implicated in triggering NF-kB-mediated expression of p53, leading to upregulation of the proapoptotic Bcl-2 family member Bax, just as cyanide-induced activation of NF-kB resulted in activation of the proapoptotic Bcl-xS and Bax proteins (Kim et al, 2002b;Shou et al, 2002). Other examples include NFkB-dependent activation of DR ligand TRAIL and TNF receptor family member DR6 (Baetu et al, 2001;Kasof et al, 2001;Rivera-Walsh et al, 2001;Siegmund et al, 2001). In one study, c-Rel induced expression of TRAIL receptors DR4 (TRAIL-R1), DR5 (TRAIL-R2) and the proapoptotic Bcl-2 family member Bcl-xS to sensitize cells to TRAIL-induced apoptosis .…”
Section: Mechanisms Through Which Nf-kb Promotes Cell Deathmentioning
confidence: 99%
“…To that extent, blocking NFB has been demonstrated to sensitize cancer cells to TNF␣-induced killing (21,41). Similarly, studies, both in vitro and in vivo, have demonstrated that pretreatment of cells with TNF␣ resulted in increased NFB activation (42,43). Recently, it has been demonstrated that endogenous production of TNF␣ is a potent trigger of NFB activation by IR.…”
Section: Discussionmentioning
confidence: 99%
“…p27, the cyclin-dependent kinase inhibitor, controls the cell cycle progression at G1 by preventing the activation of cyclin E-Cdk2 or cyclin D1-Cdk4 complexes (36,37). DR6, also known as TNFRSF21, is a member of the death receptor family, which induces apoptosis in mammalian cells and its apoptotic function is inhibited by survivin (38). Downregulation of XIAP, survivin, Hsp60 and Hsp70, as well as upregulation of BID, DR6 and p27 by cis-and transsuffruticosol D at least partially contribute to the apoptotic effect of cis-and trans-suffruticosol D.…”
Section: Discussionmentioning
confidence: 99%